2002
DOI: 10.1074/jbc.m200429200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of an Endosome-disruptive Peptide and Its Application in Cytosolic Delivery of Immunoliposome-entrapped Proteins

Abstract: Antibody-directed liposomes (immunoliposomes) are frequently used for targeted drug delivery. However, delivery of large biotherapeutic molecules (i.e. peptides, proteins, or nucleic acids) with immunoliposomes is often hampered by an inefficient cytosolic release of entrapped macromolecules after target cell binding and subsequent endocytosis of immunoliposomes. To enhance cytosolic drug delivery from immunoliposomes present inside endosomes, a pH-dependent fusogenic peptide (diINF-7) resembling the NH 2 -ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(98 citation statements)
references
References 44 publications
1
94
0
1
Order By: Relevance
“…PEGliposomes (PEG-L) without an antibody attached were used as a control. Due to the PEG-layer surrounding these liposomes, the cellular association and uptake by OVCAR-3 cells is low as shown previously (9,19).…”
Section: Liposome Characteristicsmentioning
confidence: 93%
See 1 more Smart Citation
“…PEGliposomes (PEG-L) without an antibody attached were used as a control. Due to the PEG-layer surrounding these liposomes, the cellular association and uptake by OVCAR-3 cells is low as shown previously (9,19).…”
Section: Liposome Characteristicsmentioning
confidence: 93%
“…This delivery system mimics the intracellular invasion strategy of the pathogen Listeria monocytogenes which uses LLO to escape from the endosomes (6)(7)(8). Coencapsulation of a fusogenic peptide derived from the influenza virus hemagglutinin resulted in efficient cytosolic delivery of liposomal diphtheria toxin A-chain as reported by Mastrobattista et al (9). Kakuda et al demonstrated that the insertion of cholesterol derivatized GALA-peptide into the liposomal bilayer also stimulated release of liposomal contents into the cytosol (10).…”
Section: Introductionmentioning
confidence: 89%
“…A similar strategy has been explored by Mastrobattista et al [7], who have demonstrated that coencapsulation of a pH-dependent fusogenic peptide (diINF-7) and diphtheria toxin A chain (DTA) in nonpH-sensitive immunoliposomes promotes cytosolic delivery of the encapsulated macromolecule. This peptide (resembling the NH 2 -terminal domain of influenza virus hemagglutinin HA-2 subunit) was used because functional characterization studies showed its ability to induce fusion between liposome membranes and leakage of liposome-entrapped compounds when exposed to low pH.…”
Section: Co-encapsulation Of Synthetic Fusogenic Peptides and Therapementioning
confidence: 99%
“…This peptide (resembling the NH 2 -terminal domain of influenza virus hemagglutinin HA-2 subunit) was used because functional characterization studies showed its ability to induce fusion between liposome membranes and leakage of liposome-entrapped compounds when exposed to low pH. Moreover, co-encapsulation of diINF-7 into DTA-containing immunoliposomes resulted in drastically increased cytotoxicity toward ovarian carcinoma cells, indicating that this peptide can be used to obtain cytosolic delivery of liposomeentrapped drugs with poor membrane permeation capacities [7].…”
Section: Co-encapsulation Of Synthetic Fusogenic Peptides and Therapementioning
confidence: 99%
See 1 more Smart Citation